Sustaining Transmission in Different Host Species: The Emblematic Case of Sarcoptes scabiei. (27th October 2021) - Browne, Elizabeth; Driessen, Michael M; Cross, Paul C; Escobar, Luis E; Foley, Janet; López-Olvera, Jorge R; Niedringhaus, Kevin D; Rossi, Luca; Carver, Scott
Abstract: Some pathogens sustain transmission in multiple different host species, but how this epidemiologically important feat is achieved remains enigmatic. Sarcoptes scabiei is among the most host generalist and successful of mammalian parasites. We synthesize pathogen and host traits that mediate sustained transmission and present cases illustrating three transmission mechanisms (direct, indirect, and combined). The pathogen traits that explain the success of S. scabiei include immune response modulation, on-host movement capacity, off-host seeking behaviors, and environmental persistence. Sociality and host density appear to be key for hosts in which direct transmission dominates, whereas in solitary hosts, the use of shared environments is important for indirect transmission. In social den-using species, combined direct and indirect transmission appears likely. Empirical research rarely considers the mechanisms enabling S. scabiei to become endemic in host species—more often focusing on outbreaks. Our review may illuminate parasites' adaptation strategies to sustain transmission through varied mechanisms across host species.